Job strain and arteriosclerosis in three different types of arteries among male Japanese factory workers - Michikawa, Takehiro; Nishiwaki, Yuji; Nomiyama, Tetsuo; Uemura, Takamoto; O’Uchi, Toshihiro; Sakurai, Haruhiko; Omae, Kazuyuki; Takebayashi, Toru (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'This study evaluated the association between job strain and subclinical indicators of arteriosclerosis simultaneously in the cerebral artery, the aorta, and the carotid artery. ' ' METHODS ': 'The participants in this cross-sectional study consisted of 352 male factory workers between the ages of 24.9 to 55.8 (mean 41.7) years who had not been exposed to any hazardous chemicals in Japan. Job strain was measured using a Japanese version of the Job Content Questionnaire developed by Karasek. The following subclinical indicators of arteriosclerosis were examined by noninvasive procedures: hyperintense spots in T2-weighted images in brain magnetic resonance imaging (MRI), pulse wave velocity of the aorta, and the stiffness parameter of the carotid artery using ultrasound and systolic and diastolic blood pressure. ' ' RESULTS ': 'After control for potential confounders, high job strain was associated with an increased prevalence of hyperintense spots (adjusted odds ratio 2.53, 95% confidence interval 1.14–5.63), and elevated pulse-wave velocity (adjusted increase in percent 3.5, 95% confidence interval 0.0–6.9). The stiffness parameter tended to be elevated in the high job-strain group although this trend was not statistically significant. Job strain showed no relation to blood pressure. ' ' CONCLUSIONS ': 'In this study, job strain was associated with subclinical indicators of arteriosclerosis in different arteries although the association was not statistically significant for the carotid artery. New information is offered by brain MRI for arteriosclerosis in the cerebral artery. An increase in hyperintense spots may explain the link between job strain and cerebrovascular disease.
Keywords: aorta; arteriosclerosis; brain magnetic resonance imaging; carotid artery; cerebral artery; cross-sectional study; factory worker; Japan; job content questionnaire; job strain; magnetic resonance imaging; man; MRI